(untitled) (Ibrahim Cardiac Medical Journal, 2020)
Background & objective: Rapid urbanisation in the 20th century has been accompanied by the development of slums. Nearly one-third of the world’s population and > 60% of urban populations in the least developed countries including hundreds of millions of children live in slums. Slums are areas of broad social and health disadvantage to children and their families due to extreme poverty, overcrowding, poor water quality and sanitation, substandard housing, limited access to basic health and education services. The objective of this study was to assess the demographic and nutritional status of working slum children in Dhaka city. Methods: This descriptive cross-sectional study was conducted at Moghbazar slum, situated in Dhaka city from July to December, 2013. A total of 200 slum children aged 6 to18 years whose parents’ (either father or mother) voluntarily consented to allow their children participate in the study. Result: Out of 200 slum children, 57(28.5%) were in the age group of 12-14 years, among them 110(55.0%) were male. More than 50% never attended any kinds of formal school. Forty five percent children lived with their parents. Over half (26%) of the slum children were engaged in beggary, 23% were van/rickshaw puller, 22% were rag-picker (Tokai), 10% were cooli. Three-quarters of the children had medium work-load and 80% did 5-8 hours work per day sixty percent of the children had monthly income of Taka 1000-1500. In terms of BMI, one-third (33.5%) was severely under-nourished, 55% were of normal BMI and 11.5% were overweight and obese. Conclusion: The study presented a gloomy picture (in terms of nutritional status) of working children in a selected slum within Dhaka city. Therefore, health related programmes should focus to improve the overall wellbeing of the working slum children. Ibrahim Card Med J 2019; 9 (1&2): 49-53